Microstructural Evolution of Intermetallic Compound Between SN100C Solder and ENIMAG Substrate During Isothermal Ageing - Awang Azman, Dayang Izzah Nabilah; Narayanan, Pavithiran; Y. Kozutsumi,; Osman, Saliza Azlina (International Journal of Integrated Engineering, 2024)
SN100C alloy emerges as a promising candidate when introducing lead-free solder alternatives due to its mechanical properties and solderability. The study aims to explore interfacial reactions between SN100C solder and ENIMAG surface finish. Methods involve preparing ENIMAG substrates, solder paste application, and reflow processes following JEDEC standards. Isothermal ageing treatments were conducted, and interfacial reactions were characterized using top surface and cross-section analyses via Optical Microscope (OM), Scanning Electron Microscope (SEM), and Energy Dispersive X-ray (EDX). Post-reflow, distinct IMC layers formed at the SN100C/ENIMAG solder joint's interface, evolving with ageing. Further analysis via cross-section confirms the initial formation of (Ni, Cu)3Sn4 layer followed by (Cu, Ni)6Sn5, each exhibiting varying appearance and thicknesses. Isothermal ageing increases IMC thickness, which is particularly influenced by Cu diffusion. The thickening of IMCs at the SN100C/ENIG solder joint is attributed to ENIMAG's silver content, which hinders IMC growth.